The Pedagogical Potential of Dr. Seuss’s Rhymes for Literacy and Socio-Environmental Awareness - Geni Kurniati; Christy Tisnawijaya (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study investigates how the distinctive rhyme schemes in selected Dr. Seuss’s picture books serve a dual purpose: developing early literacy and fostering socio-environmental awareness among young learners. While Seuss’s works are widely recognized for their linguistic playfulness, this paper specifically focuses on how his prosodic structures facilitate vocabulary acquisition, phonemic awareness, and the retention of complex ecological messages. Adopting a qualitative approach through literary analysis and ecocriticism, this paper examines ten picture books by Seuss spanning from 1937 to 1990. The findings indicate that rhythmic patterns do not merely serve as scaffolds for reading skills; they also act as mnemonic devices that make socio-environmental themes—ranging from inclusivity to environmental stewardship—more engaging and memorable. By integrating literary analysis with educational and environmental perspectives, this paper demonstrates that rhyme is a pedagogical strategy rather than a mere stylistic choice. Ultimately, this study illuminates how Seuss’s rhymes empower young readers to internalize critical thinking about their surroundings, serving as an effective medium for integrating literacy education with character development.